Development of TOUCH VOLLEY - volleyball tactical support system - Shigenaga, T.; Ezaki, N.; Hirotsu, N.; Miyaji, C. (The Engineering of Sport 5, Volume 2, 2004)
We have developed TOUCH VOLLEY. It is a tactical support system for volleyball by using two laptop personal computers connected by wireless LAN. Each computer can implement by using a touch sensor function on display. The developed system consists of three modes: Data input, Tactical support and Match analyzing. The input item on Data input mode is as follows; `Service and Receiving` and `Spiking and Digging `. The user can input the game data on a traj ectory of service and spiking by touching the display directly. The fundamental input procedure is as follows; 1) Input the number of players who served and spiked by touching a player button on display. 2) Input the position where the player spiked or served by touching court position directly. 3) Input received position. 4) Input receiving player. The user can use this system easily during the game because of the only four steps. It is needed only one match for the user to get familiarized with inputting game data. Moreover, the user can choose next four items as the need arises: `Evaluation of Service and Receive`, `Kinds of Attacking`, `Evaluation of Blocking` and `Evaluation of Digging`. The Tactical support mode is run during the game. This function receives a game data from connected Data input computer by wireless LAN. The team coach can see the direction chart on spike (or service) trajectory of each player immediately. Therefore, the player can get advice about their weak point or rival team. After the game, the user can analyze the game data in detail by using Match Analyzing mode. The Data analysis function shows us each player's skill with using tables anddiagram of spike (or service) trajectory. The members can research on their team and rival team. The user can get accustomed to input operation of this system easily and exactly.